Drinking water to reduce alcohol craving? A randomized controlled study on the impact of ghrelin in mediating the effects of forced water intake in alcohol addiction. (November 2017) - Koopmann, Anne; Lippmann, Katharina; Schuster, Rilana; Reinhard, Iris; Bach, Patrick; Weil, Georg; Rietschel, Marcella; Witt, Stephanie H.; Wiedemann, Klaus; Kiefer, Falk
Highlights: Forced water intake is a very useful skill for coping with alchohl craving. Forced water intake reduces acetylated ghrelin in alcoholics. Reduction of ghrelin plasma concentration is accompanied by craving reduction. Modulation of the ghrelin system is a possible new target for treatment of craving. Abstract: Background: Recent data suggest that ghrelin is involved in the pathophysiology of alcohol use disorders, affecting alcohol self-administration and craving. Gastric ghrelin secretion is reduced by stomach distension. We now tested the hypothesis whether the clinically well-known effects of high-volume water intake on craving reduction in alcoholism is mediated by acute changes in ghrelin secretion. Methods: In this randomized human laboratory study, we included 23 alcohol-dependent male inpatient subjects who underwent alcohol cue exposure. Participants of the intervention group drank 1000 ml of mineral water within 10 min directly thereafter, compared to the participants of the control group who did not. Craving and plasma concentrations of acetylated ghrelin were measured ten times during the 120 min following the alcohol cue exposure session. Results: In the intervention group, a significant decrease in acetylated ghrelin in plasma compared to the control group was observed. This decrease was correlated to a reduction in patients' subjective level of craving. In the control group, no decrease of acetylated ghrelin in plasma and no association between alcohol craving and changes in plasma concentrations of acetylated ghrelin were observed. Conclusions: Our results present new evidence that the modulation in the ghrelin system by oral water intake mediates the effects of volume intake with craving reduction in alcohol use disorders. Hence, in addition to pharmacological interventions with ghrelin antagonists, the reduction of physiological ghrelin secretion might be a target for future interventions in the treatment of alcohol craving.